Guillain-Barré Syndrome following weight loss: a review of five diet-induced cases and nineteen bariatric surgery cases - Wu, Qiong; Li, Fang-Yi; Hu, Jue; Xu, Wei; Feng, Tie-Qiao; Zhou, Hua-Shan; Wang, Zhen; Zeng, Wen-Gao (Frontiers in Neurology, 2025)
IntroductionObesity is a worldwide health concern frequently addressed by weight reduction strategies, including bariatric surgery and restricted diets. While effective, these approaches can result in complications, including Guillain-Barré Syndrome (GBS), a rare but serious autoimmune disorder. This study aims to analyze clinical and neurophysiological features of diet-induced GBS and compare them to cases linked with bariatric surgery.MethodsWe retrospectively reviewed medical records of five patients admitted to our institution between August 2012 and August 2022, who developed GBS during active dieting resulting in significant weight loss. Clinical presentations, laboratory results, neurophysiological findings, and nutritional status during treatment were analyzed. Additionally, we performed a literature review comparing these cases with nineteen previously reported instances of bariatric surgery-associated GBS.ResultsAll five patients exhibited acute, symmetrical limb weakness primarily affecting the lower extremities, accompanied by diminished tendon reflexes. Neurophysiological assessments revealed axonal damage in all cases, and albuminocytologic dissociation was present in two patients. Three patients received intravenous immunoglobulin (IVIG) therapy, while the remaining two underwent nutritional therapy alone. All patients achieved full recovery within 6 months. Notably, the rate of weight loss observed significantly exceeded recommended safe guidelines.DiscussionRapid and substantial weight loss may play a role in triggering GBS, possibly due to nutritional deficiencies or immune dysregulation. Clinicians should recognize the potential neurological risks associated with aggressive weight-loss strategies. Early diagnosis and appropriate intervention are crucial for favorable outcomes and preventing complications.